A prospective study on the co-relation between blood group and sleeping hours - Muhammad Imran Qadir; Aqsa Tahir (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2018)
Objective of present study was to correlate blood grouping with sleeping hours. Total subjects were 191. Add drop of water on slide sterilize your finger. Took needle and then prick upper portion of your finger make three spots on slide. Add small amount of antisera A, B and D. Mix it and after few second identify blood group. Subjects were the students of Bahauddin Zakariya University Multan, Pakistan. We asked question from them and organized data. In female, A+ blood group takes more sleep while AB- takes less sleep. In male B+ blood group take more sleep while O- and AB- take less.